Plastination: A Novel Way of Preservation of Cadaveric Specimens for Teaching and Learning Human Anatomy - Nurunnabi, Abu Sadat Mohammad; Alim, Abdul; Hoque, Md Mesbahul; Askary, Samia (Mediscope, 2023)
Plastination is a preservation method of anatomical specimens, which can be used for long-term educational purposes both in basic and clinical sciences. Dr. Gunther von Hagens first developed this technique in 1977 in Heidelberg, Germany. There are several plastination methods that are currently used in different countries. Room-temperature silicone plastination using ‘North Carolina technique’ is assumed as the best suited for our institutions considering our country’s climate and feasibility in terms of limited resources. In general, plastination methods involve four stages: i) fixation and specimen preparation; ii) dehydration and defatting; iii) plastic permeation or force impregnation by plastic material; and iv) hardening or curing. Fixation involves addition of formalin to the specimen for preventing decay and bacterial growth. Then dehydration is done by submerging the specimen in acetone baths. Thereafter, the specimen is kept in a vacuum chamber, where plastic permeation or forced impregnation occurs. Polymers penetrate the tissues of the specimen while removing acetone. After leaving the specimen in an airtight chamber maintaining a specific temperature, hardening or curing process follows. Plastination technique has several advantages like making cadaveric specimens easy to handle, easy storage of viscera, prolonged preservation, odourless, dry, non-irritant, nontoxic presentation and ability to present more anatomical details than ever before. Some important drawbacks are that the process is very costly, time consuming, limited size of the impregnation chamber, health and environmental hazards of the chemicals used. Plastination seems to have a great future in all fields of teaching, training and research not only in anatomy education but also in other disciplines in medical, biomedical, veterinary and health science institutions across the globe. Plastinates have opened several new windows to the world of anatomical sciences. Mediscope 2023;10(1): 31-37